2019
DOI: 10.1515/psicl-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

A comparative investigation of metadiscourse in English and Persian architectural research articles

Abstract: The present article reports a comparative study of interactional metadiscourse markers in English and Persian research articles. Drawing on Hyland’s (2005) interpersonal model of metadiscourse, this study investigates the employment of “hedges”, “boosters”, and “attitude markers” in a corpus composed of the post-method sections of 100 research articles (50 English and 50 Persian) in the field of architecture. Overall, it was found that there are statistically significant differences between the frequencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Some articles coalesced the results and discussion sections, others contained other sections such as applications and conclusions (Lin & Evans, 2012). Focusing on the "post-method" sections of the articles, however, enabled the researcher to offer a comprehensive view of the persuasive and argumentative language used in research articles (Ariannejad, et al, 2019;Cao & Hu, 2014). The next issue which needs to be added is that the compiled articles were all published in the leading international journals of architecture to reassure the high quality of the academic language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles coalesced the results and discussion sections, others contained other sections such as applications and conclusions (Lin & Evans, 2012). Focusing on the "post-method" sections of the articles, however, enabled the researcher to offer a comprehensive view of the persuasive and argumentative language used in research articles (Ariannejad, et al, 2019;Cao & Hu, 2014). The next issue which needs to be added is that the compiled articles were all published in the leading international journals of architecture to reassure the high quality of the academic language.…”
Section: Methodsmentioning
confidence: 99%
“…Or exclusive first person plural pronouns 'we' and its objects and possessives are used to show the active involvement of the writer in the research process and emphasizing on his role as an active member of the disciplinary community (Carciu, 2009). Research has revealed discipline-specific features in the employment of self-mentions in research articles (Ariannejad, et al, 2019;Dong & Qiu, 2018;MurDuenas, 2011;Hyland, 2001). In this regard, some researchers have conducted cross-disciplinary investigation on the employment of these features in academic articles (Munoz, 2013;Salas, 2015), while others have had more in-depth investigations on the use of self-mentions and merely focus on a specific discipline (Yang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These few studies conducted on conference abstracts are not enough to provide a comprehensive understanding of the use of metadiscourse in conference abstracts. Although other researches on hedging and boosters in recent times exist (Afreh et al, 2017;Salar & Behzad, 2016;Ariannejad et al, 2019;Zali et al, 2020), there are but a few studies that deal with the subject in conference abstracts. One can hardly find studies that deal with the use of hedges and boosters in hard sciences and soft sciences conference abstracts, hence the need for the current study.…”
Section: Earlier Studies On Metadiscourse Elements (Hedges and Booste...mentioning
confidence: 99%
“…Overall, it was found that there are measurably noteworthy contrasts between the frequencies of Hedges, Boosters, and Attitude Markers utilized in English and Persian sub-corpora. Ariannejad et al (2019) expressed that their findings "provide deep insights into the rhetorical conventions and norms in architectural articles and offer a broader perspective towards discoursing patterns and persuasion strategies of English and Iranian academic writers in this field".…”
Section: Previous Studiesmentioning
confidence: 99%